Detailed Examples of Figure Preparation in the Two Most Common Graph Layouts - Gorgol, Izolda; Salwa, Hubert (Applied sciences, 2025)
Graphs are an excellent tool with applications in various branches of engineering. Graph layouts have emerged as a cornerstone in the visual representation and analysis of complex systems. They are indispensable in reducing complexity, optimizing designs, improving communication, and enhancing problem-solving capabilities. They transform abstract concepts and data into visual formats that are easier to interpret, analyze, and apply in real-world engineering challenges. Therefore, many graph layouts are designed for various purposes. It is not easy to choose the most appropriate one. There are a number of surveys on this subject, but they are descriptive ones. In this paper, we focus on the two most versatile—and therefore most widely used—layouts, namely Fruchterman–Reingold and ForceAtlas2, and show their possibilities in a visual way. We compare how the drawings appear while using various settings of the available options. This helps to choose an appropriate set of settings in practice.